1996
DOI: 10.1200/jco.1996.14.2.593
|View full text |Cite
|
Sign up to set email alerts
|

Significance of cytogenetic findings for the clinical outcome in patients with T-cell lymphoma of angioimmunoblastic lymphadenopathy type.

Abstract: This is the first study that seems to indicate that cytogenetic findings have prognostic significance in AILD-type T-cell lymphoma. These results must be proven in prospective studies of homogeneously treated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
28
1
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 19 publications
0
28
1
2
Order By: Relevance
“…Several recurrent breakpoints were noted in all three PTCL subgroups, including regions previously associated with B-and T-cell lymphoma, such as 1p36, 6q21, 7p15, 11q13, 14q11.2, 14q32, 17p13, 19q13, 22q11.2 and 22q13 (Berger et al, 1988;Inwards et al, 1990;Kaneko et al, 1988;Lepretre et al, 2000;Michaux et al, 1996;Schlegelberger et al, 1994aSchlegelberger et al, ,b, 1996. Recurrent breakpoints were also observed at 16q22 and 16q24, regions not currently associated with lymphoma.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Several recurrent breakpoints were noted in all three PTCL subgroups, including regions previously associated with B-and T-cell lymphoma, such as 1p36, 6q21, 7p15, 11q13, 14q11.2, 14q32, 17p13, 19q13, 22q11.2 and 22q13 (Berger et al, 1988;Inwards et al, 1990;Kaneko et al, 1988;Lepretre et al, 2000;Michaux et al, 1996;Schlegelberger et al, 1994aSchlegelberger et al, ,b, 1996. Recurrent breakpoints were also observed at 16q22 and 16q24, regions not currently associated with lymphoma.…”
Section: Discussionmentioning
confidence: 95%
“…Although the karyotypes are complex among uncategorized PTCL, frequent rearrangements involving chromosomes 1, 6q, 14q11, 7p, 7q, 9p, and 10p have been reported (Berger et al, 1988;Inwards et al, 1990;Kaneko et al, 1988;Lepretre et al, 2000;Schlegelberger et al, 1994aSchlegelberger et al, ,b, 1996. Recurrent abnormalities noted among specific subtypes of PTCL include the t(2;5)(p23;q35) and other translocation variants in ALKpositive ALCL (Wellmann et al, 1995;Rosenwald et al, 1999), and trisomies of 3 and 5 in AITL (Schlegelberger et al, 1994b(Schlegelberger et al, , 1996. Comparative genomic hybridization (CGH) studies analyzing two out of the three main subtypes of PTCL have also been recently reported (Zettl et al, 2004;Thorns et al, 2007).…”
mentioning
confidence: 99%
“…Moreover, except for some cytogenetic results, such as the presence of an additional X chromosome, structural aberrations of the short arm of chromosome 1 and complex karyotypes, associated with a poor prognosis, 13 little is known about the prognostic impact of chromosome abnormalities in T cell NHL. This lack of information is also evident when it comes to CGH studies, while there are different reports about the CGH profile in B-NHL, there are no studies of T-NHL series that have looked for gains or losses of DNA sequences in the genome of these lymphomas.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known regarding predictors of spontaneous remission; however, one study showed factors that might predict this event (11). It showed that having an extra third chromosome was associated with a higher chance of spontaneous remission (P = 0.02) and an extra X chromosome showed an insignifi cant trend for less chance of remission (P = 0.09).…”
Section: Discussionmentioning
confidence: 99%
“…Th e spontaneous remission of AITL without therapy is quite unusual and, although not unknown to the medical literature (9)(10)(11), is still a very rare occurrence. Little is known regarding predictors of spontaneous remission; however, one study showed factors that might predict this event (11).…”
Section: Discussionmentioning
confidence: 99%